2023
DOI: 10.3390/children10101663
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Physical Activity, Mediterranean Diet and Emotional Intelligence in Spanish Primary Education Students

Daniel Sanz-Martín,
Félix Zurita-Ortega,
Pilar Puertas-Molero
et al.

Abstract: There is an international social concern about the low levels of physical activity among young people. It is essential to know what factors influence the practice of physical activity in order to design effective proposals for health promotion. The study aims to: (1) classify primary school students according to their levels of out-of-school physical activity, Mediterranean diet, emotional attention, emotional clarity and emotional repair; (2) analyse descriptively and correlationally the adolescents’ profiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 50 publications
(58 reference statements)
2
3
0
Order By: Relevance
“…García-Pérez et al (2023) showed that 37.5% of law, social work and psychology students had low adherence to the Mediterranean diet and 39.7% had medium adherence. The dietary levels of Spanish university students are in line with those obtained for other population groups (Sanz-Martín et al, 2023a). Sanz-Martín et al (2023a) showed that 11.6% of primary school students had low adherence to the Mediterranean diet, 56.66% had medium adherence and 31.74% had high adherence.…”
Section: Introductionsupporting
confidence: 82%
See 4 more Smart Citations
“…García-Pérez et al (2023) showed that 37.5% of law, social work and psychology students had low adherence to the Mediterranean diet and 39.7% had medium adherence. The dietary levels of Spanish university students are in line with those obtained for other population groups (Sanz-Martín et al, 2023a). Sanz-Martín et al (2023a) showed that 11.6% of primary school students had low adherence to the Mediterranean diet, 56.66% had medium adherence and 31.74% had high adherence.…”
Section: Introductionsupporting
confidence: 82%
“…The dietary levels of Spanish university students are in line with those obtained for other population groups (Sanz-Martín et al, 2023a). Sanz-Martín et al (2023a) showed that 11.6% of primary school students had low adherence to the Mediterranean diet, 56.66% had medium adherence and 31.74% had high adherence.…”
Section: Introductionsupporting
confidence: 82%
See 3 more Smart Citations